(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Women play an integral role in the society, there health and well-being are vital in such journey, certain health conditions like endometriomas often affect the quality of life of many women. These endometriomas are cystic lesions that stem from endometriosis. And are most commonly found in the ovaries. Ovarian endometrioma is the most common form of endometriosis, with its prevalence ranging between 17% and 44%. The clinical challenges include persistent pain, dysmenorrhea, and infertility, all of which adversely affect women’s quality of life and their ability to reproduce. In Ayurveda, this condition is comparable to Udavartini Yonivyapad, a known gynecological disorder. It has a significant prevalence among women, reflecting its widespread impact on female reproductive health. Methods: Case study of a 30-year-old married woman came with severe pain during menstruation along with prolonged bleeding during cycles in the last 4 years and the patient was initially diagnosed with an ovarian endometrioma through sonography before she approached us. Based on the Lakshanas and Nidana Panchaka it was diagnosed as Udavartini Yonivyapad. This case was effectively managed using Shodhana therapy combined with internal medications. Results: Following Shodhana her condition exhibited signs of improvement, and there was noticeable reduction in the size of endometrioma. Conclusion: This case is an example to explain the Ayurveda’s role in managing such disease conditions by demonstrating the improvement in the pain and size of the endometrioma which was confirmed by a sonography before and after the treatment